The risk of finding focal cancer (less than 3 mm) remains high on re-biopsy of patients with persistently increased prostate specific antigen but the clinical significance is questionable. - Zackrisson, B; Aus, G; Bergdahl, S; Lilja, H; Lodding, P; Pihl, C; Hugosson, J (2004)
PURPOSE: We evaluated the significance of focal prostate cancer found in sextant biopsies in men participating in a biennial prostate specific antigen (PSA) based screening program. MATERIALS AND METHODS: In 1995, 10000 men 50 to 65 years old were randomized to biennial screening with PSA testing. Sextant biopsies were recommended when total PSA was 3 ng/ml or greater at screening rounds 1 and 2, and 2.54 ng/ml or greater at subsequent screening rounds. Focal cancer was defined as total a core cancer length of less than 3 mm in the biopsy specimen. Low volume cancer was defined as a total tumor volume of less than 0.5 cm in the radical retropubic prostatectomy specimen. RESULTS: The number of men who underwent biopsy and the number of cancers detected in the 5 possible sets of biopsies were 1725 and 402, 706 and 124, 307 and 36, 103 and 9, and 13 and 0, respectively. The risk of detecting focal cancer was 7.9%, 10.2%, 7.5%, 5.8% and 0%, respectively, but the relative ratio (focal-to-all cancers) increased 34%, 58%, 64%, 67% and, not applicable, respectively. In men with a total core cancer length of less than 10 mm there was no correlation between core cancer length and total tumor volume, as measured in the prostatectomy specimen. Two-thirds of men with a total core cancer length of less than 3 mm had a tumor volume of greater than 0.5 cm, while the risk of low volume cancer was less than 5% only in men with a total core cancer length of greater than 10 mm. CONCLUSIONS: In a repeat PSA based screening program sextant biopsies are of little or no value for predicting tumor volume.